ISGE statement on oral emergency contraception. (October 2014) - Glasier, Anna; Gemzell-Danielsson, Kristina; Bouchard, Philippe; Genazzani, Andrea R.; Al-Azzawi, Farook; Berga, Sarah; Birkhaeuser, Martin; Brincat, Mark; De Melo, Nilson R.; Foidart, Jean Michel; Kenemans, Peter; Lunenfeld, Bruno; et al.
Abstract Unintended pregnancy is an important public health problem worldwide. Unwanted pregnancies may end in induced abortion (legal or illegal, safe or unsafe) or in childbirth. In many parts of the world both can be life threatening. Even where both are safe, abortion is distressing for all concerned while unwanted births often lead to poor health and social outcomes for both the mother and her child.